(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The norteña music, known to be the one who characterize fundamen- tally the Norwest of the Mexican Republic, it is one of the integral ele- ments of the national identity. Their songs, rhythms, instruments, spaces and practices form part of the tradition that identifies a geografic region. From the Mexican Independence it has tried to build and homogenize a “national” identity, at which it has been provided of significations that tend to “erase” the particularities of the regions. With the national or local identity exists the gender identity, also constructed historically. In the second half of the XX century, the growth of the media allowed that this identities permeate in the social imaginary. From above we ask, what types of generic identities for men and women the popular Mexi- can music known as the northern music propose? When we put in game the category of northern music with the one of gender, we consider, it could reveal some of the mechanism from which, culturally, are reprodu- ce the speeches that tend to perpetuate a cultural system. We propose that the Mexican Norteña music tends not only to reproduce but also to exacerbate the traditional prototypes of male and submissive woman.